PROTOTYPE DOUBLE BUBBLE IMPINGER (IGG) Performance at Boiler Flue Gas Measurement PS II PT. Pertamina (Persero) RU III Plaju-Sungai Gerong Measurement) - ST.,M.T., Hilwatullisan (KINETIKA, 2011)
The conscious of society with air pollution because flue gas from sourch of pollutant in big city is increasing. From any do not move sourch although from move sourch. So, it need the alternative equipment to monitoring and measuring the hazardous gas. One of them is using double bubble impinger system, it can measure 4 paramaters like NOx, SOx, H2S and NH3. The method is using in analyze absorp solution in IGG based on Indonesia National standart in 2005. the test of IGG in Boiler PS II Pertamina RU III Plaju. The result of measurement there was different value between emission gas concentration from Pertamina and IGG. Concentration of gas emission derived from IGG were 15,54 ppm, 4,74 ppm, 0,11 ppm, 0,053 ppm whereas Pertamina were 3 ppm, 1 ppm, 0 ppm dan 0 ppm. Based on measuring the performance both IGG and AUER Pump Detector & Tube could not be compare because the differences of measuring showed the significant value.